Pregnancy course and outcomes in women with arrhythmogenic right ventricular cardiomyopathy. Issue 4 (30th December 2015) - Hodes, Anke R; Tichnell, Crystal; te Riele, Anneline S J M; Murray, Brittney; Groeneweg, Judith A; Sawant, Abhishek C; Russell, Stuart D; van Spaendonck-Zwarts, Karin Y; van den Berg, Maarten P; Wilde, Arthur A; Tandri, Harikrishna; Judge, Daniel P; et al.
Abstract : Objectives: To characterise pregnancy course and outcomes in women with arrhythmogenic right ventricular dysplasia/cardiomyopathy (ARVD/C). Methods: From a combined Johns Hopkins/Dutch ARVD/C registry, we identified 26 women affected with ARVD/C (by 2010 Task Force Criteria) during 39 singleton pregnancies >13 weeks (1–4 per woman). Cardiac symptoms, treatment and episodes of sustained ventricular arrhythmias (VAs) and heart failure (HF) ≥ Class C were characterised. Obstetric outcomes were ascertained. Incidence of VA and HF were compared with rates in the non-pregnant state. Long-term disease course was compared with 117 childbearing-aged female patients with ARVD/C who had not experienced pregnancy with ARVD/C. Results: Treatment during pregnancy (n=39) included β blockers (n=16), antiarrhythmics (n=6), diuretics (n=3) and implantable cardioverter defibrillators (ICDs) (n=28). In five pregnancies (13%), a single VA occurred, including two ICD-terminated events. Arrhythmias occurred disproportionately in probands without VA history (p=0.045). HF, managed on an outpatient basis, developed in two pregnancies (5%) in women with pre-existing overt biventricular or isolated right ventricular disease. All infants were live-born without major obstetric complications. Caesarean sections (n=11, 28%) had obstetric indications, except one (HF). β Blocker therapy was associated with lower birth weight (3.1±0.48 kg vs 3.7±0.57 kg; p=0.002). During follow-up children remained healthy (median 3.4 years), and mothers were without cardiac mortality or transplant. Neither VA nor HF incidence was significantly increased during pregnancy. ARVD/C course (mean 6.5±5.6 years) did not differ based on pregnancy history. Conclusions: While most pregnancies in patients with ARVD/C were tolerated well, 13% were complicated by VA and 5% by HF.